The effectiveness of using duolingo as an interactive learning media - Zahra Chasanah, Aliyah; Halim, Abdul (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
Interactive learning media is a flexible approach that enables students to learn individually. Due to the wide range of interactive learning programs like Duolingo, teachers are increasingly relying on these platforms. This study utilizes an Experimental research methodology, which involves modifying or measurement of variables, the specification of the sample or population to be examined, the selection of a suitable sampling method, the selection of a data collection and analysis approach, and the determination of the necessary statistical test. The sample comprised 30 students from Muhammadiyah Istiqomah 1 Senior High School, who were selected using random sampling. The participant currently enrolled in language classes and should not have any previous experience with Duolingo. The study included pre-test and post-test measures, consisting of 4 sections derived from Duolingo, specifically targeting English language proficiency in speaking, writing, and reading. After implementing Duolingo as a new interactive learning tool, we conducted pre-test and post-test assessments to evaluate students performance. The researchers assessed the statistical significance of the result by employing T-test in SPSS. The result showed there was significantly increase in students vocabulary before and after Duolingo intervention as an Interactive learning media, the researchers also proved using Duolingo as an additional learning media was effective to helped students to improving their speaking skills.